1996
DOI: 10.1128/aac.40.3.750
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral efficacy in vivo of the anti-human immunodeficiency virus bicyclam SDZ SID 791 (JM 3100), an inhibitor of infectious cell entry

Abstract: SID 791, a bicyclam inhibiting human immunodeficiency virus (HIV) replication in vitro by blocking virus entry into cells, is an effective inhibitor of virus production and of depletion of human CD4+ T cells in HIV type 1-infected SCID-hu Thy/Liv mice. Steady levels of 100 ng of SID 791 or higher per ml in plasma resulted in statistically significant inhibition of p24 antigen formation. Daily injections of SID 791 caused a dose-dependent decrease in viremia, and this inhibition could be potentiated by coadmini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Based on its promising antiviral efficacy in cell cultures and in the in vivo SCID-hu Thy/Liv model (Datema et al, 1996) and the SCID-hu PBMC model (D. Schols, unpublished observations), AMD3100 has recently entered clinical studies. A phase I trial unveiled no signs of toxicity (Hendrix et al, 2000), and the therapeutic potential of the compound is currently being evaluated in a phase II study with patients infected with HIV.…”
mentioning
confidence: 99%
“…Based on its promising antiviral efficacy in cell cultures and in the in vivo SCID-hu Thy/Liv model (Datema et al, 1996) and the SCID-hu PBMC model (D. Schols, unpublished observations), AMD3100 has recently entered clinical studies. A phase I trial unveiled no signs of toxicity (Hendrix et al, 2000), and the therapeutic potential of the compound is currently being evaluated in a phase II study with patients infected with HIV.…”
mentioning
confidence: 99%
“…An isolate of HIV-1 selected in vitro for resistance to AMD3100 and displaying cross-resistance to heparin, dextran sulfate, and other polyanionic compounds was found to have mutations in gp120 (44). AMD3100 also showed some antiviral activity in the scid-hu thy/liv mouse model, suggesting the possibility that AMD3100 might work as an antiviral agent in humans (46). Results of a phase I safety and pharmacokinetic study of AMD3100 in healthy volunteers were recently reported (47).…”
Section: Cxcr4 Inhibitor Amd3100mentioning
confidence: 94%
“…In fact, it was shown that AMD3100 had antiviral activity in vivo before its interaction with CXCR4 was known. The drug proved efficacious, alone and in combination with other anti-HIV drugs in achieving a marked reduction in viral load in HIV-1-infected SCID-hu Thy/Liv mice [89]. Interestingly, the authors used a clinical HIV-1 isolate (called EW), which very likely used CXCR4 to enter and infect the cells.…”
Section: Bicyclamsmentioning
confidence: 96%
“…The outgrowth of the R5 viruses is apparently due to the selective inhibitory action of AMD3100 against CXCR4-mediated virus entry, and cannot be attributed to co-receptor switching, since specific antiviral resistance to AMD3100 resulting from serial passage in vitro did not result in alterations in co-receptor usage [101]. Among the HIV coreceptor antagonists, the bicyclam AMD3100 was the most advanced in studying viral replication in vivo in HIV-1-infected SCID-hu Thy/Liv and SCID-hu PBMC mouse models [88,89]. Later, in a phase I clinical trial with AMD3100, healthy volunteers were given AMD3100 as a single 15 min.…”
Section: Clinical Perspectivesmentioning
confidence: 99%